Impact of Biomass Burning Plumes on Photolysis Rates and Ozone Formation at the Mount Bachelor Observatory. Issue 4 (18th February 2018) - Baylon, P.; Jaffe, D. A.; Hall, S. R.; Ullmann, K.; Alvarado, M. J.; Lefer, B. L.
Abstract: In this paper, we examine biomass burning (BB) events at the Mt. Bachelor Observatory (MBO) during the summer of 2015. We explored the photochemical environment in these BB plumes, which remains poorly understood. Because we are interested in understanding the effect of aerosols only (as opposed to the combined effect of aerosols and clouds), we carefully selected three cloud‐free days in August and investigate the photochemistry in these plumes. At local midday (solar zenith angle (SZA) = 35°), j (NO2 ) values were slightly higher (0.2–1.8%) in the smoky days compared to the smoke‐free day, presumably due to enhanced scattering by the smoke aerosols. At higher SZA (70°), BB aerosols decrease j (NO2 ) by 14–21%. We also observe a greater decrease in the actinic flux at 310–350 nm, compared to 360–420 nm, presumably due to absorption in the UV by brown carbon. We compare our measurements with results from the Tropospheric Ultraviolet‐Visible v.5.2 model. As expected, we find a good agreement (to within 6%) during cloud‐free conditions. Finally, we use the extended Leighton relationship and a photochemical model (Aerosol Simulation Program v.2.1) to estimate midday HO2 and RO2 concentrations and ozone production rates ( P (O3 )) in the fire plumes. We observe that Leighton‐derived HO2 and RO2 values (49–185 pptv) and instantaneous P (O3 ) (2.0–3.6 ppbv/h) are higher than the results from the photochemical model. Plain Language Summary: Biomass burning can emit huge amounts of aerosol particles and trace gases to the atmosphere. These plumes are rich in nitrogen oxides and volatile organic compounds that can react with sunlight to produce ozone, a greenhouse gas and a health hazard to sensitive individuals. However, photochemistry in biomass burning plumes is poorly understood. While most studies rely on model simulations, there are very few in situ measurements aimed at investigating how these aerosols affect photolysis rates. Our study aims to fill this knowledge gap. We use measurements from a mountaintop station in central Oregon (Mount Bachelor Observatory, 2.8 km above sea level) and run a box model to verify our estimates of radicals and ozone production rates. Our results show that biomass burning aerosols increase photolysis rates during midday and decrease the rates during early morning/late afternoon. The ozone production rates derived from the photochemical model are in the same order of magnitude but lower than our calculations. In our paper, we present explanations for the discrepancies between measured and modeled values. Key Points: Biomass burning (BB) aerosols increase local noontime j (NO2 ) At high solar zenith angle, BB plumes decrease j (NO2 ) by 14–21% We calculate 49–185 pptv of HO2 and RO2 in BB plumes and an instantaneous O3 production rate of 2.0–3.6 ppbv/h